Two-level Evaluation of Public Transport Performances - Matulin, Marko; Mrvelj, Štefica; Jelušić, Niko (Promet - Traffic&Transportation, 2012)
The focus of this paper is evaluation of public transport (PT) performances. For this purpose the focus is on quantitative performance attributes of tramway network and two levels of the evaluation analysis are defined – the micro and macro level analysis. The two-level evaluation analysis can be used to solve the problem of ambiguity in conclusions about PT performances. The ambiguity appears when the set of collected data is incomplete, misinterpreted, partially analyzed or when some background impacts are neglected. For each level of analysis a set of performance indicators is defined and their mathematical formulations are presented. The selection of indicators is based on the analysis of expected events on the PT vehicle’s itinerary. The applied data collection methodology, necessary for testing of proposed evaluation approach, is described and the results are presented and discussed. It has been found that for a specific case the two-level evaluation analysis can be important for the control of PT performances and transport planning.KEY WORDS: evaluation, public transport performance, micro and macro level analysis, quality of service